ArrayMining: a modular web-application for microarray analysis combining ensemble and consensus methods with cross-study normalization - Glaab, Enrico; Garibaldi, Jon; Krasnogor, Natalio (BioMed Central Ltd, 2009)
Background: Statistical analysis of DNA microarray data provides a valuable diagnostic tool for the investigation of genetic components of diseases. To take advantage of the multitude of available data sets and analysis methods, it is desirable to combine both different algorithms and data from different studies. Applying ensemble learning, consensus clustering and cross-study normalization methods for this purpose in an almost fully automated process and linking different analysis modules together under a single interface would simplify many microarray analysis tasks.